Arquitectura e Estrutura: Duas faces da mesma folha de papel - Liliana Borges Ribeiro (2016)
"Architecture and Structure: Two faces of the same paper", is a study that focus on the poetic relationship between architecture and engineering. It is understood as example, one side that represents the architectural design, the inspiration, the art, the creativity, and on the verse, the structural design based on mathematical rigor of structural calculation, the rationality, the efficiency, in other words the accuracy that justifies particular expression of architectural design. At first sight, the architectural and engineering professions are as close as distant and in this regard, there is the intention to deepen the connection between them. The challenge of this study is to show four distinct and paradigmatic works, the way the architectural design and structural design develop and relate or contradict each other, along the path between the first draft and the finished building. The four works under consideration are: the Sydney Opera House, the Pavilion of Portugal, Braga Municipal Stadium and Central China Television. It is a theoretical work, which is assumed to be a personal interest in the research of this subject. Divided into six moments, it begins with a contextualization from the iron architecture up to Modern Movement, through the analysis of the four case studies, and ends with a reflection which intend to synthesize the most relevant ideas of the analysis and leave open questions about the future of the relationship between the two professions.